Ethical perfection in Buddhist soteriology - Keown, D; Keown, Damien V. (1986)
﻿ The extent of the ethical component in the Buddha's teachings is often commented upon but has received disproportionately little attention from scholars. This thesis is intented to make a contribution in this area by (i): examining the substantive content of Buddhist ethical categories; (ii) locating ethics and the goal of ethical perfection in the context of the overall soteriological framework elaborated by the Buddha; (iii) offering a characterisation of the formal structure of Buddhist ethics according to the typology of philosophical ethical theory. The scope of the enquiry will include ethical data from both the Small and Large Vehicles. Previous research has concentrated almost exclusively on the Theravāda system and this has resulted in a truncated presentation of Buddhist ethics which has failed to reveal the underlying structure and its development through time. The present discussion therefore proceeds in a roughly chronological sequence in the selection of its data, considering first of all material from Theravādin sources (both Canonical and commentarial) and passing on to an investigation of the systematisation of ethical categories in the Abhidharma of the Small Vehicle as found in the scheme of the Sarvāstivāda preserved in the Abhidharmakośa. Subsequently, in Chapter 4, an account of Mahayana ethics is offered drawing mainly on the Śila-paṭala of the Bodhisattvabhūmi. The final two chapters (5 and 6) discuss two influential theories of ethics elaborated in the Western tradition which bear a prima facie resemblance to the theoretical structure of Buddhist ethics. Chapter 5 will deal with Utilitarianism and its resemblance to Buddhism, and Chapter 6 will be devoted to the Aristotelian ethical system. My conclusion will be that the Aristotelian model provides the closest analogue to Buddhism and a preliminary attempt will be made to pursue certain points of contact as an indication of the direction for future research. The overall argument, which is cumulative throughout the thesis, will be that ethical perfection in Buddhism is an integral and inalienable component in the perfection of human nature envisaged and attained by the Buddha. This, together with the intellectual perfection epitomised by the attainment of insightful knowledge (paññā). constitutes the Summum Bonum or complete good for man.